A Prospective Study on Exchange Transfusion in Neonatal Unconjugated Hyperbilirubinemia – in a Tertiary Care Hospital, Nepal - Malla, T.; Singh, S.; Poudyal, P.; Sathian, B.; BK, G.; Malla, K.K. (Kathmandu University Medical Journal, 2017)
Background An exchange transfusion involves replacing patient’s blood with donor blood in order to remove abnormal blood components and circulating toxins while maintaining adequate circulating blood volume. Objective To observe the incidence, causes of jaundice requiring Exchange and any adverse event of exchange transfusion in newborns with unconjugated hyperbilirubinemia. Method Prospective study undertaken at Neonatal Intensive Care Unit (NICU) of Manipal Teaching Hospital, Pokhara, Nepal from March 2014 to April 2015. For both mothers and neonates blood group and Rh typing and for all newborns pre and post exchange complete blood count with peripheral smear, serum bilirubin, hemoglobin, calcium, potassium, random blood sugar, C-reactive protein and blood culture and where ever required Direct Coombs test, reticulocyte count, G6PD activity and thyroid function test were done. The incidence, indications, positive outcome, complications and mortality were noted. Result Out of 481 cases of unconjugated hyperbilirubinemia 29(6%) required exchange transfusion. 55.2% Pathological Jaundice [13.8% ABO incompatibility, sepsis and hypothyroidism was commonest causes] and 44.8% exaggerated physiological jaundice [27.6% with no underlying pathology, 10.3% preterms 3.4% cephalhematoma] required exchange transfusion. Post transfusion, bilirubin level decreased significantly (p<0.001). The commonest adverse events noted were anemia (89.7% / p<0.018), hyperglycemia(51.7% / p<0.001), hypocalcaemia (48.3% /p<0.001)), sepsis(10.3%), hypernatremia (13.8%), hyperkalaemia, bradycardia, apnea and feed intolerance (6.9%). None of them had kernicterus and there was no mortalities. Conclusion Exchange transfusion is an effective procedure to decrease bilirubin levels but is associated with many complications. Hypothyroidism was one of the commonest cause of jaundice requiring Exchange transfusion.